ANALISIS CAMEL TERHADAP PROFITABILITAS BANK PERKREDITAN RAKYAT (Students' Journal of Accounting and Banking, 2012)
This research is aim to test the effect of the effect of variables Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operating Ratio (BOPO) and Loan to Deposit Ratio (LDR) toward Profitability of Bank Perkreditan Rakyat.Data that used in this research is Bank Perkreditan Rakyat Kabupaten Demak that published at Bank Indonesia in the period of December 2010 – September 2011. Technical analysis that used was multilinier regression and the hypotheses test used t-statistik to test coefficient partial regression and F-statistic to test the effect all together with level of significance 5%. And also carry out classic assumption test that includes normality test, multicolinierity test, autocorrelation test and heteroskedasticity test.From the results of hypothesis test (F test) show that CAR, NPL, BOPO and LDR all together has a significant effect to ROA, whereas CAR, NPL, BOPO and LDR has a significant effect to ROE. And according to partial test result (t test) in this research show that CAR and NPL doesn’t have significant effect to ROA. Whereas BOPO and LDR has significant effect to ROA. And according to partial test result (t test) in this research shows that CAR doesn’t have significant effect to ROE. Whereas NPL, BOPO and LDR has significant effect to ROE.Keywords : Profitability (ROA and ROE), CAR, NPL, BOPO, LDR